Procedure for Handling 4-H Accounts: Guidelines for Fund-Raising - Marilyn N. Norman; Joy C. Jordan (EDIS, 2007)
4H5.5, a 4-page factsheet by Marilyn N. Norman and Joy C. Jordan, gives guidelines for properly conducting fundraising within 4-H. Published by the UF Department of Family, Youth and Community Sciences, February 2007.